(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The goal of advertising is the persuasion of a customer of the merits of a particular product or service. Whatever the strategy advertisers employ in order to influence the consumer, language is the main carrier of the message. Among the components of advertising (visual images, words, logos, brand names, graphic designs and so on), words play a key role since by them the audience is able to grasp the advertising message. This article highlights the importance and types of metaphors as one of the most potent persuasion tactics in advertising communication, and it contributes to our understanding of the persuasive influence of various forms of metaphors in print advertising.